Evaluation of the predictive value of red blood cell distribution width for onset of cerebral infarction in the patients with obstructive sleep apnea hypopnea syndrome - Shen, Chang-Xing (Medicine (Baltimore), 2017)
Red blood cell distribution width (RDW) is a risk factor for the complications caused by obstructive sleep apnea hypopnea syndrome (OSAHS). This study was aimed to evaluate the predictive value of RDW for the occurrence of cerebral infarction in patients with OSAHS. We conducted a prospective study of 129 consecutive patients who were admitted to the Sleep Laboratory of in the Tenth People's Hospital of Shanghai (China) with complaints of snoring, apnea, or daytime sleepiness. All patients underwent polysomnography between June 2011 and May 2012. In total, 90 patients met the study criteria and were included in the study; there are 71 men and 19 women. RDW correlated positively with the apnea hypopnea index (AHI) (P = .00, r = 0.76). Logistic regression analysis showed correlations between each variation and cerebral infarction, high blood pressure (odds ratio [OR] = 4.72, P = .220), diabetes (OR = 2.67, P = .490), hyperlipidemia (OR = 7.42, P = .190), RDW (OR = 58.24, P = .020), and AHI (OR = 243.92, P = .001). RDW ≥ 15% showed a higher predictive value for the occurrence of cerebral infarction in patients with OSAHS (area under curve 0.837; sensitivity 0.919; specificity 0.755), with positive and negative predictive values of 0.697 and 0.938, respectively. RDW correlates positively with AHI. RDW values ≥15% are predictive for the occurrence of cerebral infarction in patients with OSAHS.